A REVIEW: THE EFFECT OF OPERATING CONDITIONS AND THERMAL MANAGEMENT ON THE PERFORMANCES OF METAL HYDRIDE HYDROGEN STORAGE TANK - Taurista Perdana Syawitri (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2016)
For safety and operability concerns, the use of metal hydrides to store hydrogen appears to be particularly promising option for alternative energy at present. However, the process of adding, removing and distributing heat during the hydrogen charging/ discharging process is problematic due to the poor effective thermal conductivity of the metal hydride porous bed and the high enthalpies of H2 adsorption/desorption. Therefore, heat transfer is a critical factor affecting the performance of metal hydride hydrogen (MHR) storage tanks. Over decade, many researches focused on MHR’s operating conditions and its thermal management to improve its performance.